2020
DOI: 10.25259/ajir_31_2019
|View full text |Cite
|
Sign up to set email alerts
|

Packing density and long-term occlusion after transcatheter vessel embolization with soft, bare-platinum detachable coils

Abstract: Objective: The objective of this study was to examine packing density and long-term recanalization rates after embolization with soft, bare-platinum ruby coils in the gastroduodenal artery (GDA). Materials and Methods: Retrospective case review of patients with hepatic malignancy who underwent coil occlusion of the GDA for radioembolization or hepatic arterial infusion chemotherapy between November 2013 and July 2018. Data on patient demographics, GDA diameter, length of coil pack, and distance between GDA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…The volume of the inserted coils was calculated using the formula for the volume of a cylinder, assuming the coil to be a thin and infinitely long cylinder (Volume=π×radius 2 ×length). For the calculation of the vessel volume, we measured the length of the coil-filled segment using two-dimensional angiography [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The volume of the inserted coils was calculated using the formula for the volume of a cylinder, assuming the coil to be a thin and infinitely long cylinder (Volume=π×radius 2 ×length). For the calculation of the vessel volume, we measured the length of the coil-filled segment using two-dimensional angiography [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the calculation of the vessel volume, we measured the length of the coil-filled segment using two-dimensional angiography. 7 Statistical analyses were conducted using the Wilcoxon signed-rank test. A two-sided P-value of 0.05 was used in this study.…”
Section: Image Analysis and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In coherence, using computer-generated aneurysmal models to simulate hemodynamics, recurrent aneurysms had significantly lower coil packing density and higher uncoiled aneurysmal volume, the latter of which was an independent predictor for recurrence [3]. Vogler et al corroborated this, demonstrating a high success rate of occlusion from the use of high-packing density coils [27]. However, a study in Japan found that aneurysm volume (odds ratio (OR): 15.3; P < 0.001) and residual volume (OR: 30.9; P < 0.001) were significant predictors for recanalization, not packing density (OR: 0.98; P = 0.341) [6].…”
Section: Discussionmentioning
confidence: 94%